Domain wall creep motion dynamics in CoFeB nanowire strips of different thicknesses using micromagnetic simulation approach - Nugraha Raditya; Djuhana Dede; Kurniawan Candra (ITM Web of Conferences, 2024)
Field-induced domain wall motion on thin magnetic films with perpendicular anisotropy has long been attributed with the universal creep theory, in which the domain wall (DW) is able to experience a slow-moving motion with driving fields below the depinning threshold. Despite the numerous research that has been conducted in regards to this phenomenon, creep motion thus far has yet to be observed on a typical single-layered magnetic film. The effects of the film’s thickness towards the creep motion are also scarcely explored. In this study, we conduct micromagnetic simulations of CoFeB nanowire strips with perpendicular anisotropy and varying thicknesses to investigate the dynamics of the creep motion being exhibited. We then analyze the obtained DW velocities and its’ agreement with the universal creep law equation. The velocities obtained with low driving fields is found to be in an agreement with the creep law equation. The varying thicknesses also seem to affect the overall DW velocity and DW width.